FORMULATION AND EVALUATION OF FLOATING MATRIX TABLETS OF LEVOFLOXACIN HEMIHYDRATE USING HYDROXYPROPYL METHYLCELLULOSE K4M TO TREAT HELICOBACTER PYLORI INFECTION - Baratam, Srinivasa Rao; J, Vijayaratna (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of the study was to develop a floating drug delivery system of levofloxacin (LVF) hemihydrate for sustained drug delivery to improve the extended retention in the stomach, oral bioavailability, and local site-specific action in the stomach. Methods: Preparation of LVF tablets using melt granulation method using hydroxypropyl methylcellulose (HPMC) K4M with sodium bicarbonate as gas generating agent. From LFTA1 to LFTA5, formulations were developed and evaluated for floating properties for swelling characteristics and in vitro drug release studies. In vitro dissolution was carried out using USP II paddle method using 0.1N HCI pH buffer at 50 rpm and samples were measured at 294 nm using ultraviolet-visible spectroscopy. Results: Obtained Fourier-transform infrared charts indicated that there is no positive evidence for the interaction between LVF and ingredients of the optimized formula. In vitro drug release was performed and drug release kinetics were evaluated using the linear regression method and were found to be followed the zero-order release by diffusion controlled release. Optimized formula was found to be LFTA4 with 20% of a polymer with 99.03% of drug release with 12 h of floating time and 32 s floating lag time. Conclusion: Matrix tablets (LFTA4) formulated employing 20% HPMC K4M are best suited to be used for gastroretentive dosage form of LVF.